2017
DOI: 10.7899/jce-16-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of practice variability on spinal manipulation learning*

Abstract: Objective: To evaluate the effects of practice variability on chiropractic students' capacity to deliver spinal manipulations (SMs) of a targeted peak force. Methods: Forty students participated in an experimental session including either a variable or a constant practice protocol of 45 SMs. SMs were delivered on a computer-connected device that recorded force-time profiles. Ten SMs with a target peak force of 350-N were performed before practice, immediately following practice, and 2 days later. Mixed-design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…27 Compared with posteriorto-anterior thoracic mobilization, our preload data are comparable to the force magnitude of grade IV mobilization that is considered the grade level before the thrust achievement defined as grade V. 9 Regular use of manipulative procedure is essential in developing manual skills, and several studies have attested to the significance of practice training to improve accuracy (targeted force level) and consistency in manipulation performances. 13,28 The results obtained herein confirmed that some preload difference exists between students and TPs but not for all. This small discrepancy may be explained by various individual learning processes and skills acquisition between the fifth-year students during their educational program as previously suggested by Loranger et al 29 Similarly, Enebo et al 30 demonstrated the benefit of practice training on spinal manipulation performance and competency.…”
Section: Reaction Force Orientationsupporting
confidence: 72%
“…27 Compared with posteriorto-anterior thoracic mobilization, our preload data are comparable to the force magnitude of grade IV mobilization that is considered the grade level before the thrust achievement defined as grade V. 9 Regular use of manipulative procedure is essential in developing manual skills, and several studies have attested to the significance of practice training to improve accuracy (targeted force level) and consistency in manipulation performances. 13,28 The results obtained herein confirmed that some preload difference exists between students and TPs but not for all. This small discrepancy may be explained by various individual learning processes and skills acquisition between the fifth-year students during their educational program as previously suggested by Loranger et al 29 Similarly, Enebo et al 30 demonstrated the benefit of practice training on spinal manipulation performance and competency.…”
Section: Reaction Force Orientationsupporting
confidence: 72%
“…Interestingly, the S-A group increased its peak force during the retention block (block 3), but increased the difference between the target force and the peak force applied, which can be considered a performance decrease. Although previous study have shown that small regimen of augmented feedback can improve SM learning [ 7 , 15 , 16 ], the limited number of practice trials with augmented feedback for each force target may have been insufficient to trigger learning effects. Moreover, according to the guidance hypothesis, augmented feedback can lead to error corrections and subsequent learning but providing inadequate feedback (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between student and experienced clinician thrust duration suggests there may be a difference in how students, who are still learning subtle coordination aspects of HVLA-SM, adapt to and learn the ability to deliver prescribed forces compared to clinicians whose motor skills are perhaps more ingrained. Marchand et al 22 noted that the level of preload force applied was predictive of loading rate, suggesting that training prescribed preload force together with peak force may lead to an increased consistency of thrust duration. 22 Additional study is needed to better understand these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Marchand et al 22 noted that the level of preload force applied was predictive of loading rate, suggesting that training prescribed preload force together with peak force may lead to an increased consistency of thrust duration. 22 Additional study is needed to better understand these phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation